The Effect of ‘Power’ as an Instructional Writing Strategy on Students’ Writing Skill Across Gender - Rany Prihastuti, Luh Putu; Padmadewi, Ni Nyoman; Ramendra, Dewa Putu (Journal of Education Reseach and Evaluation, 2020)
The study aimed at: (1) investigating the effect of POWER as an instructional writing strategy on students’ writing skill; (2) analyzing the different effect of POWER across gender; and (3) analyzing problems of writing faced by the students. The explanatory design was applied in this study. A writing post-test was used to obtain the data and were analyzed using One-Way ANOVA. The findings of the study revealed that (1) there was a significant effect of POWER on students’ writing skill: p = .001 with a large effect size (eta = .17); (2) there was a significant difference on the effect of POWER on the students’ writing skill across gender: p = .013 with a large effect size (eta = .18); and (3) the males struggled in editing and revising rather than females. Then, those resulted in the differences quality of their writing, in which point female participants surpassed the males. Therefore, teachers are expected to implement POWER as one of their variants in EFL writing instruction